PERLINDUNGAN HUKUM TERHADAP KONSUMEN PRODUK KOSMETIK ILEGAL DI KOTA PADANG - Sommaliagustina, Desi; Harniwati, Harniwati; Nugraha, Edo (JOURNAL OF INDONESIAN COMPARATIVE OF SYARIAH LAW, 2024)
There are many cosmetics on the market today with various types of brands in line with women's desire to always look beautiful. This is then exploited by irresponsible business actors by producing or trading cosmetics that do not meet the requirements for distribution to the public. Not a few women are interested in buying products at low prices but with fast visible results. So many women choose shortcuts to buy a product even though the cosmetics they buy do not meet the requirements and are not registered with BPOM. It is not uncommon for these illegal cosmetics to be obtained at affordable prices because there is no distribution permit number from BPOM. There is no cosmetic raw material label, and there is no product expiration date. Because the price is cheap and can be purchased easily, cosmetics without a distribution permit are easily consumed by the public. Consumers' ignorance of the side effects of cosmetics containing dangerous ingredients is one of the reasons many women continue to use illegal cosmetics. Consumers usually do not research a product before buying, this is also one of the factors that causes cosmetic products containing dangerous ingredients to still be in demand by many women. They generally buy cosmetic products without prior consideration considering that the products they buy have direct side effects. The data analysis method used is sociological juridical.